A Deadly Electrocardiography Shark Fin Sign in ST Elevation Myocardial Infarction: A Case Report - Syahwina Inayasari; Luhur Pribadi; Margono Gatot Suwandi (GLOBAL HEALTH SCIENCE GROUP, 2025)
Shark fin ECG pattern, also known as 'giant R waves', or 'triangular QRS-ST-T waveform' is a high-risk ECG pattern associated with ST-elevation myocardial infarction (STEMI). Shark fin ECG is typically accompanied by occlusion of the left main coronary artery and the left anterior descending artery, and it is considered to be related to a high risk of death through cardiac arrest and cardiogenic shock. Objective: This case report aims to present a case study of a patient with acute coronary syndrome st-elevation myocardial infarction with a shark fin ECG pattern. Methods: The method used is a descriptive case report design conducted on one subject. Data were collected by conducting interviews, assessments, and therapy for one patient with a shark fin ECG sign in ST-Elevation myocardial infarction. Data analysis compared the results with the theory and previous study. Results: The result of this study indicated that Mr. X aged 44 years, was in cardiac arrest and unstable hemodynamic, and experienced a return of spontaneous circulation (ROSC) after he was given 45 minutes of cardiopulmonary resuscitation (CPR), and the electrocardiography result showed shark fin sign and extensive anterior st elevation, the patient then underwent primary percutaneous intervention and the coronary catheterization showed total occlusion in left anterior descending artery (LAD), proximal stenosis 20% in the left circumflex artery (LCx), and proximal stenosis 30% in the right coronary artery (RCA). The drug-eluting stent was finally placed in the LAD. Conclusions: Shark fin sign ECG pattern indicates total occlusion and a large area of transmural ischemia, and predicts high mortality, early recognition and prompt aggressive treatment can reduce the risk of more serious complications and mortality.